2015
DOI: 10.1111/jnc.13249
|View full text |Cite
|
Sign up to set email alerts
|

Structure, function and toxicity of alpha‐synuclein: the Bermuda triangle in synucleinopathies

Abstract: Parkinson's disease belongs to a group of currently incurable neurodegenerative disorders characterized by the misfolding and accumulation of alpha-synuclein aggregates that are commonly known as synucleinopathies. Clinically, synucleinopathies are heterogeneous, reflecting the somewhat selective neuronal vulnerability characteristic of each disease. The precise molecular underpinnings of synucleinopathies remain unclear, but the process of aggregation of alpha-synuclein appears as a central event. However, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
165
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 184 publications
(168 citation statements)
references
References 215 publications
3
165
0
Order By: Relevance
“…246 High resolution ion-mobility mass spectroscopy has revealed that HPLC-purified αS is autoproteolytic, giving rise to a number of small molecular weight fragments upon incubation. In particular, the fragment of residues 72–140 contains majority of the NAC region and aggregates faster than full-length αS.…”
Section: Alpha-synuclein and Parkinson’s Diseasementioning
confidence: 99%
“…246 High resolution ion-mobility mass spectroscopy has revealed that HPLC-purified αS is autoproteolytic, giving rise to a number of small molecular weight fragments upon incubation. In particular, the fragment of residues 72–140 contains majority of the NAC region and aggregates faster than full-length αS.…”
Section: Alpha-synuclein and Parkinson’s Diseasementioning
confidence: 99%
“…LNs are abnormal neuronal processes (axons or dendrites) that contain α-syn aggregates with a more diffuse α-syn morphology than LBs. LBs and LNs are the primary pathological features of the Lewy body diseases (LBD) (229, 230). In addition, aggregated α-syn is also a major constituent of oligodendrocyte glial cytoplasmic inclusions (GCIs) found in MSA (231).…”
Section: α-Synucleinopathiesmentioning
confidence: 99%
“…Aggregation of α -synuclein is a critical step in the etiology of PD, with prefibrillar oligomers of the protein that might constitute the direct precursors of fibrils being involved in neurodegenerative process [87, 88]. Even if the injection of fibrils into the rat brain is found to be more toxic than that of oligomers and ribbons, as it induces neurodegeneration and motor impairment, all these species can self-amplify in vivo and lead to PD/multiple system atrophy-like alterations in the injected animals [89].…”
Section: Toxicity Of α-Synuclein Oligomers and Fibrils: A Still Unmentioning
confidence: 99%